A new species of the lichen moth genus Tigricollis Singh & Kirti, 2016 (Lepidoptera: Erebidae: Arctiinae) from eastern Indonesia - Spitsyn, Vitaly M.; Spitsyna, Elizaveta A.; Bolotov, Ivan N. (Zootaxa, 2021)
N/A